Carboxymethyl guar gum synthesis in homogeneous phase and macroporous 3D scaffolds design for tissue engineering. (1st July 2018) - Kundu, Sonia; Das, Aatrayee; Basu, Aalok; Ghosh, Debjani; Datta, Pallab; Mukherjee, Arup
Graphical abstract: Highlights: High DS carboxymethyl guar gum was synthesized in homogeneous phase. Macrofibrous 3D porous scaffolds were designed from CMGG-PVA blends following a facile gas foaming technique. Cell proliferation in CMGG-PVA scaffolds was unrestricted. CMGG-PVA scaffolds were appropriate for tissue engineering. Abstract: Guar gum (GG) is a galactomannan obtained directly from the C yamopsis tetragonoloba seeds pericarb. The biopolymer hydrates hugely in three chain associated coil formations. Chaotropic Hofmeister ion like lithium interacts at the hydrogen bonding sites and render GG homogenization in polar solvents like dimethyl sulfoxide. This phenomenon was used for the first time for galactomannan derivatisations in homogeneous phase. Higher degree of substitution (DS) that was hereto unattainable in GG was achieved due to Hofmeister ion assisted assembly deformations. Furthermore, carboxymethyl guar gum (CMGG, DS = 1.10) blends well in poly-vinyl alcohol (PVA) at 2:1 mass ratio and enabled hydrophilic porous scaffold design for cell propagation. CMGG-PVA scaffolds porosity was 70–90% and the tensile strength was 6.32 MPa. CMGG-PVA scaffolds were useful as cell factories and in tissue engineering. New generation guar gum derivative scaffolds were non cytotoxic and permitted cell propagation in growth medium.